A study on the antecedents and consequences of customer delight. (2nd January 2017) - Dey, Soma; Ghosh, Sanjukta; Datta, Biplab; Barai, Parama
Abstract : This study explores the synergistic impact of surprise, joy, interest and captivation in creating customer delight during six different attractive moments-of-truths (MTs) in full service restaurants in Kolkata. Six attractive service MTs were identified using Kano et al.'s model [(1984 ). Attractive quality and must quality. Journal of Japanese Society for Quality Control, 14 (2), 39–48.]. The antecedents of customer delight and its consequence, that is, customer loyalty, were measured using a 31-item Likert-type questionnaire. Structural equations modelling was done to examine whether surprise, interest, joy and captivation led to customer delight thereby resulting in customer loyalty. It was found that joy and captivation led to customer delight. Customer delight in-turn led to customer loyalty.